Beyond Posters and Pennants: College-Going Messaging at Three Racially and Economically Diverse Public Schools. Issue 11 (November 2019) - Martinez, Melissa A.; Torres, Isaac; Lewis, Katherine
Context: It has been argued that high schools with a majority of students of color and from low-income backgrounds must be purposeful in fostering a college-going culture in order to address the challenges and inequities historically underserved students face in preparing for and accessing a higher education. However, what this looks and sounds like in practice is not always clear, leaving schools seeking common ground on how to create a college-going environment. Purpose: Through a symbolic and ecological model of college readiness framework, the messaging associated with the college-going culture at three racially and economically diverse Texas high schools that had consistently high college ready graduate rates was examined. The research questions that guided the study included: What types of college-going culture messages are conveyed at the schools, and how? How might such messaging impact students, school staff and leaders? Research Design: This study drew on data from a three-year, multi-site descriptive case study of three public high schools in different regions of Texas that all served approximately 50% or more of students with financial need and 72% to 97% students of color, specifically Latina/o and Black students. Data Collection and Analysis: Data was collected during week-long, yearly visits to the three schools and included: school and district documents; individual and group semi-structured interviews with 194 individuals including administrators, teachers, support staff, students, parents, and community members; observations of common areas and classrooms; archival data; and researcher-derived documents including field notes, memos, and photographs of the school grounds and school activities. This paper primarily drew on the pictures taken of the schools (in hallways, classrooms, and shared spaces like cafeterias and libraries), field notes, memos, and interview data that specifically spoke to the visual and verbal messaging associated with the college-going culture. Analysis of data revealed six themes: college is a revered goal with many options; varying degrees of integration; support and resources are at your reach; think college and career; finding funding for college is vital; college is an individual and shared success. Conclusions: This study's findings suggest the need to: reconsider what a strong college-going culture entails, re-envision college-going cultures as dynamic, multi-layered, and responsive, reframe postsecondary opportunities so they are more expansive and varied, and re-evaluate inequities in college-going messaging and academic rigor.